The Effectiveness of Machine Translation Systems in Translating English Fixed Phrases into Arabic - Abdou Ahmed Ali Mounassar (University of Science and Technology, Sana’a, Yemen, 2024)
The purpose of this study is to investigate the effectiveness of machine translation systems in translating English fixed phrases into Arabic. The study uses a qualitative approach to translate 25 English fixed phrases into Arabic using four machine translation systems. The translations are then compared and analyzed along with four well-known sources: Al-Mawrid Dictionary by Baalbaki (1993), Dictionary of Comparative Proverbs by Mourad (2006), Dictionary of Common English Proverbs by Attia (2004), and Ghazala's (2008) translations. The study found all systems struggled with accuracy. The main problems were poor translations, loss of figurative meaning, inappropriate equivalents, and the Arabic sentences seemed to be distorted in terms of forms and contents. The study indicates that adding cultural knowledge bases into translation systems can greatly improve their ability to understand and translate complex fixed phrases.